Temuan Klinis dan Terapi Dini pada Anak dengan Sindrom Ramsay-Hunt - Noerfani, Rahma Rafina; Budianti, Windy Keumala; Permatasari, Nadya Aninditha; Gifani, Fathya Nabila (Jurnal Kedokteran Meditek, 2025)
Introduction: Ramsay-Hunt syndrome is a complication of the varicellazoster virus that causes inflammation of the geniculate ganglion cranial nerve VII. This disease is a rare case in children. This case report aims to highlight the importance of diagnosis, early examination, and appropriate therapy to prevent complications and poor prognosis. Case Illustration: A 9 year-old girl presented with clear fluid-filled blisters in her left ear for four days before going to the hospital. Two days after the lesions came out, she complained of her face feeling tilted to the right, difficulty close her left eye, and the corner of her mouth being more drawn towards the normal side. The left auricular helix fossa region showed a rash of multiple vesicles in groups containing clear fluid with an erythematous skin base, distributed unilaterally according to the dermatome. The patient was diagnosed with Ramsay-Hunt syndrome. She was treated with a combination of oral acyclovir and methylprednisolone injections. Discussion: Antiviral therapy within 24– 72 hours after the onset of the rash is very effective for healing of the rash and reducing the duration of pain. Corticosteroid as an antiinflammatory can reduce peripheral nerve damage and edema. Combination of corticosteroid with acyclovir for 7 days in herpes zoster accompanied by facial paralysis is very effective in significantly reducing acute pain and reducing the risk of complications. Conclusion:The exact diagnosis and combination of antiviral with corticosteroid therapy in children can be beneficial in reducing the duration of lesions and pain as well as the risk of complications.